Pulsed electric field ablation process—a study of the effect of different shapes (materials) of metal stents on the ablation effect - Wang, Zhen; Liang, Ming; Sun, Jingyang; Zhang, Jie; Li, Yunhao; Xuan, Fengqi; Han, Yaling (Frontiers in Cardiovascular Medicine, 2025)
BackgroundArrhythmias are a common group of cardiovascular diseases, and in recent years, pulsed electric field ablation technology has made great progress in the treatment of arrhythmias. However, the effect of different materials and shapes of cardiac stents on the ablation effect at the target site during epicardial ablation has not been effectively studied.MethodsThe ablation targeting position was modeled and simplified, the ablation catheter and cardiac stent were restored in real size, and the ablation region was modeled in three dimensions using a computer. Multi-model cardiac stents were established and different materials were added to different stents, and the ablation region was effectively evaluated with a field strength of 1,000 V/cm as the contour.ResultsThe ablative electric field was present only at the ablation targeting site. In the computational simulation, the effective ablation width caused by the simplified metal stent was not significantly different from that of the real stent (the maximum difference in ablation width was 0.34 mm). The variation of the effective ablation area caused by different metals was small (for example, the ablation catheter was 0.5 mm away from the metal stent, and the width of the effective ablation area ranged from 9.79 mm to 10.13 mm). The maximum temperature change at the targeting site caused by the simplified stent of the scaffold was small (the maximum temperature after ablation was 43.88°C, and the maximum temperature after ablation of the real scaffold was 45.19°C).ConclusionThe simulation results show that the width of the targeted ablation area does not change greatly due to the shape and material of the metal stent, and the simplified metal stent model can effectively predict the effective ablation area. The metal stent has a certain warming effect on the ablation area, and the warming phenomenon of the real stent is more intense than that of the simplified stent, but this temperature change does not cause thermal damage to the targeting site.